PROBLEMA MESIN PENERJEMAH BERBASIS AI DALAM PROSES PENERJEMAHAN BUKU INGGRIS-INDONESIA DAN SOLUSINYA - Untara, Wahyu; Setiawan, Teguh (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
This research aims to find out the main problems of AI-based translation machine, Google Neural Machine Translation System (GNMT) or Google Translate, during an English-Indonesian book translation process. It also has the objective to find the solutions for the problems. To approach the translation issues, the study uses Christiane Nord’s four translation problems which consists of pragmatic translation problems, convention-related translation problems, linguistic translation problems, and text-specific translation problems. Molina and Albir’s techniques of translation are applied to fix the problems. The study uses qualitative methods to analyze the translation issues. From 5447 translated words, it is found that the main problems of Google Translate during book translation are linguistic translation problems, and there are seven translation techniques involved to deal with the problems.